Conserved ancestral tropical niche but different continental histories explain the latitudinal diversity gradient in brush-footed butterflies - Chazot, Nicolas; Condamine, Fabien L; Dudas, Gytis; Peña, Carlos; Kodandaramaiah, Ullasa; Matos-Maraví, Pável; Aduse-Poku, Kwaku; Elias, Marianne; Warren, Andrew D; Lohman, David J; Penz, Carla M; DeVries, Phil; et al. (Nature communications, 2021)
The global increase in species richness toward the tropics across continents and taxonomic groups, referred to as the latitudinal diversity gradient, stimulated the formulation of many hypotheses to explain the underlying mechanisms of this pattern. We evaluate several of these hypotheses to explain spatial diversity patterns in a butterfly family, the Nymphalidae, by assessing the contributions of speciation, extinction, and dispersal, and also the extent to which these processes differ among regions at the same latitude. We generate a time-calibrated phylogeny containing 2,866 nymphalid species (~45% of extant diversity). Neither speciation nor extinction rate variations consistently explain the latitudinal diversity gradient among regions because temporal diversification dynamics differ greatly across longitude. The Neotropical diversity results from low extinction rates, not high speciation rates, and biotic interchanges with other regions are rare. Southeast Asia is also characterized by a low speciation rate but, unlike the Neotropics, is the main source of dispersal events through time. Our results suggest that global climate change throughout the Cenozoic, combined with tropical niche conservatism, played a major role in generating the modern latitudinal diversity gradient of nymphalid butterflies.
Keywords: vznik druhů (genetika); Genes, Insect; tropické klima; extinkce biologická; biodiverzita; Genetic Speciation; časoprostorová analýza; Extinction, Biological; hmyzí geny; Spatio-Temporal Analysis; rozšíření zvířat; zvířata; zeměpis; fylogeneze; Tropical Climate; Animal Distribution; Biodiversity; Geography; Butterflies; Phylogeny; motýli; Animals